Firm sustainable development goals and firm financial performance through the lens of green innovation practices and reporting: A proactive approach - Parvez Alam Khan; Satirenjit Kaur Johl; Shakeb Akhtar (Journal of Risk and Financial Management, 2021)
The current global economy demands synergy between ecological responsiveness and proactive business models. To analyze these dynamics, the objective of this study is to simultaneously investigate the effects of green innovation practices concerning the sustainable development goals (SDG) and financial performance of firms. This study also advocates for the injection of green innovation reporting into sustainable reporting for greater disclosure. Data from sixty-seven companies from five continents and the top five blue chip firms for each country are collected through content analysis, with the generalized least squares (GLS) approach used to test a causal relationship hypothesis. The results indicate mixed findings, with green product innovation showing positive relationships with returns on equity (ROE) and returns on investments (ROI). At the same time, green process innovation shows negative relationships with returns on assets (ROA) but shows a positive impact on returns on investments (ROI) and firm SDGs. In contrast, green service innovation shows an insignificant relationship with financial performance and SDGs. On the other hand, non-operational green innovation variables and green marketing positively affect returns on assets and investment, showing significant negative impacts on returns on equity. However, green organizational innovation shows an insignificant relationship with firm financial performance and SDGs. In addition, this study also shows that the Australia/New Zealand region is the leader in green innovation reporting, followed by Europe, Asia, Africa, and lastly, North America.
Keywords: 330; green innovation; sustainable development goal; environmental policy; financial performance; green innovation disclosure